Educational role of public parks: windows to past, to future and to exotic worlds - Fekete, Albert; G. Tar, Imola; Győri, Péter; Sárospataki, Máté (4D Journal of Landscape Architecture and Garden Art, 2020)
The design of public parks in Europe evolved at the end of 18th century. The first public parks were created primarily for leisure, entertainment and social representation. Reflecting architectural and artistic trends of specific time periods and eras, and design concepts of various ideologies, through their images, compositional aspects and symbols public parks also fulfill an important educational role in everyday life. Following the progress of the theoretical background of European public parks, the article introduces the research analysis of the educational role of the parks. The conclusions drawn from the historical review and from the analysis of public parks and gardens provide a good basis for the renovation methodology of historic parks and for the design of contemporary urban parks and open spaces, with an emphasis on their current and future educational role. Placing the survey and assessment of the public parks into an international context makes it possible to overview the most important educational benefits of public parks to the society.
Keywords: public park design; landscape design; landscape architecture; late 18th century; historical review; historic parks